Programa Convivencia Escolar. Deficiencias y posibilidades frente a la atención de la violencia escolar - Bullon Velasquez, Braulio Renato (2025)
School violence is a problem that has persisted over the years both internationally and nationally. This form of oppression usually manifests itself among students or between adults and students, directly affecting the development and integral education of children and adolescents. The Peruvian State has tried to address this situation through various policies and social programs in the education sector, once the Guidance and Welfare Offices (OBE), later the School Ombudsman for Children and Adolescents (DESNNA), and, currently, the School Coexistence program. In this context, the objective of this research is to determine whether this program develops a positive intervention against this problem. For this purpose, the study was carried out in the Juan Guerrero Químper and Túpac Amaru educational institutions during the year 2022. The methodology used was of qualitative approach, based on semi-structured interviews, observation and bibliographic review that allows understanding from the perception of the student community. Finally, it is concluded that, although there are advances in the implementation of the program, important limitations persist, such as the scarce training of personnel, insufficient resources and a social and family context that intensifies cases of school violence.